Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

If 2 tan b+ cot b= tan a then prove that cot b= 2tan (a-b)

If 2 tan b+ cot b= tan a then prove that cot b= 2tan (a-b)

Grade:11

1 Answers

Arun
25763 Points
4 years ago

2tan(A - B)

2{(tanA - tanB)/(1+tanA.tanB)}

now substitute for tanA = 2tanB + cot B,

2{(2tanB + cotB - tanB)/(1 + (2tanB + cotB).tanB)}

2{(tanB + cotB)/(2 + 2tan^2B)}   (using cotB*tanB = 1)

{(tanB + cotB)/(1 + tan^2B)}

cotB{(tan^2B + 1)/(1 + tan^2B)}   (using cotB*tanB = 1)

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free